Experimental and numerical investigation on an optimization method of heaving buoy wave energy converter arrays based on a given target wave spectrum. (1st September 2022) - Gong, Haoxiang; Shi, Hongda; Han, Zhi; Cao, Feifei
Abstract: In this paper, an active optimization method of a wave energy converter (WEC) array that focuses on the characteristics of the random sea condition is proposed. Physical model tests were conducted in both regular and irregular wave conditions. Three representative regular wave cases were determined from the target wave spectrum using the method. A rigid cylindrical heaving buoy model with different constant power take-off (PTO) damping forces and drafts was applied to find the optimal isolated WEC parameter under each regular wave condition. Three equal buoys with respective optimized parameters were arranged rectilinearly into a WEC array for irregular wave tests. The power output of arrays with different settings are compared, indicating the advantages of the different optimized array and the significance of unit order. To amplify the optimization effect, a supplementary numerical investigation of a 5-body WEC array was carried out using the boundary element method (BEM). The results demonstrate the method and show the influence of the number of different units. Highlights: An optimization method of WEC array that based on the target wave spectrum is proposed. Model tests for isolated buoy and array were conducted in regular and irregular waves. Supplementary simulations of a 5-body array were executed using BEM to validate the method.